1970
DOI: 10.1037/h0029600
|View full text |Cite
|
Sign up to set email alerts
|

Group decision schemes and strategy preferences in a sequential response task.

Abstract: Four-person groups responded to a four-choice sequential decision task for three blocks of trials. Decision patterns were analyzed in terms of strategies (a plan for distributing choices across a 50-triaI block) and social decision schemes (majority, plurality, equiprobability, and highest expected value) for selecting among member strategy proposals. Predictive models, assuming each decision scheme in turn and using parameter estimates from an independent sample of individuals, were compared with group data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
0
19
1
Order By: Relevance
“…More specifically, the general social decision scheme model is a transformation of the probability distribution characterizing individual preferences to a group distribution over the same alternatives. This "individual-into-group" approach is similar in spirit to Restle and Davis' (1962) waiting-time model and Steiner's (1966) group productivity models in group problem solving, and to group decision models of Zajonc (Smoke & Zajonc, 1962;Zajonc, 1966;Zajonc et al, 1968 and Davis et al (1968Davis et al ( , 1970. However, social decision scheme theory as presented here is a general case model, extending in principle to any n and r. Moreover, the formal derivation herein led to an extremely simple expression, Equation 2, that permitted a very convenient representation (the social decision scheme matrix, D) of the hypothetical social process leading to a decision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, the general social decision scheme model is a transformation of the probability distribution characterizing individual preferences to a group distribution over the same alternatives. This "individual-into-group" approach is similar in spirit to Restle and Davis' (1962) waiting-time model and Steiner's (1966) group productivity models in group problem solving, and to group decision models of Zajonc (Smoke & Zajonc, 1962;Zajonc, 1966;Zajonc et al, 1968 and Davis et al (1968Davis et al ( , 1970. However, social decision scheme theory as presented here is a general case model, extending in principle to any n and r. Moreover, the formal derivation herein led to an extremely simple expression, Equation 2, that permitted a very convenient representation (the social decision scheme matrix, D) of the hypothetical social process leading to a decision.…”
Section: Discussionmentioning
confidence: 99%
“…In the example at hand, Davis et al (1970) found that by the third trial block, only the equiprobability model provided an acceptable account of the data. In many ways, such a finding is counter to intuition.…”
Section: Special Cases and Applications "Weight Of Opinion" Casementioning
confidence: 92%
See 1 more Smart Citation
“…Bquiprobability, in which the group response is equiprobable among all responses advocated by at least one group member, is the best-fitting social combination process on relatively uninvolving decisions, such as which of a set of lights will occur on a series of trials (e.g., Davis, Hornik, & Hornseth, 1970;Zajonc, Wolosin, Wolosin, & Sherman, 1968). Such tasks do not have demonstrablhy correct answers, and probably do not engage strong values.…”
Section: Collective Inductionmentioning
confidence: 99%
“…Charness, Karni, and Levin (2007), for instance, found that groups violate the principle of stochastic dominance in risky choice significantly less often than individuals. Davis, Hornik, and Hornseth (1970), on the other hand, rejected only the highestexpected-value process model as an adequate account of group decisions throughout a sequential choice task and observed virtually no differences between groups' and individuals' choice strategies. Contrasting sequential decisions from experience in static and dynamic choice settings, Lejarraga, Lejarraga, and Gonzalez (2014) showed that groups outperform individuals in static settings but lose their advantage when the environment changes unexpectedly.…”
Section: Discussionmentioning
confidence: 99%